Eclipse RCP and Eclipse Java IDE - Mustonen, Maija (2007)
Jyväskylä: University of Jyväskylä, 2007. 25 pages Bachelor's Thesis After it was first released in 2001, Eclipse has evolved into the most popular professional Integrated Development Environment (IDE) for the Java programming language. This thesis is a literature review of Eclipse both as a plugin based Rich Client Platform (RCP) and as a Java IDE. Data have been collected from books, scientific articles, official websites, and technical manuals. Furthermore, a simple Eclipse plug-in is introduced and the code explained. The main contribution of the thesis is to form an extensive and up-to-date description of the Eclipse phenomenon.